INTERGENERATIONAL COMMUNICATION IN SPORTS GENRE FILMS: THEMATIC ANALYSIS OF FILM ‘DANGAL’ THROUGH SEMIOTIC PRISM - Kumar, Aditya (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The research study takes a semiotic analysis of the Hindi movie Dangal (2016) to understand the function of dialogue as an audio-visual code in the lives of the most representative main characters, Mahavir Phogat and his daughters in relation to intergenerational communication. The study decodes how the spoken exchanges bring meaning at the thematic depth and bolster the progression of the denotation and connotation. The denotations totally build plot and character development while the connotative meanings unfold present undercurrents of emotion, ideological tensions, and cultural contexts. The analysis follows some crucial narrative moments in the film where dialogue catches the drama of the changing father-daughter relationship along themes of discipline, perseverance, authority, and empowerment. Drawing on selected dialogues and attaching time stamps to them, the article shows how speech is present in the narrative not just as a device but as a multi-layered semiotic system that influences character and spans generations. By treating dialogue as a linguistic and cinematic code, this study proves how speech within Dangal may further be used to inscribe public as well as personal change, making it a compendious text for semiotic and cultural analysis.